Tinjauan Yuridis Terhadap Plagiarisme Konten Youtube Yang Dilakukan Channel Calon Sarjana Kepada Youtuber Jamie Tate Menurut Undang-Undang Nomor 28 Tahun 2014 Tentang Hak Cipta - Mohammad Yusril Ramdhany (INVENTION: Journal of Intellectual Property Law, 2025)
This research aims to find out the legal protection for Jamie Tate's Youtube video copyrighted work as a foreigner against acts of plagiarism committed by the Calon Sarjana’s channel as an Indonesian citizen according to Law Number 28 of 2014 concerning Copyright and to find out the legal remedies that the creator can take for plagiarism . This research uses a type of Normative research, using two approaches, namely the legal approach (Statue Approach) and the conceptual approach (Conceptual Approach). The results of this research show that legal protection against copyright violations such as piracy of content or video content, rebroadcasting without the creator's permission, as well as plagiarism of content by both domestic and foreign individuals, so as to protect the rights of creators relating to their creations granted exclusive rights to the Creator. Meanwhile, if foreigners want to file a copyright lawsuit, they can do so at the Commercial Court as stated in Article 95 Paragraph (1) UUHC. It can be said that foreigners can sue Indonesian citizens who violate their copyright because Indonesia has ratified the Berne Convention through Presidential Decree 18/1997. So, in this case, Jamie Tate as the creator has the right to file a claim for compensation with the Commercial Court for the copyright infringement he experienced as stated in Article 99 Paragraph (1) UUHC. The legal action taken by Jamie Tate regarding acts of plagiarism carried out by the Calon Sarjana’s Youtube channel can be done in 3 ways, namely, through litigation by suing the Bachelor Candidate in the Commercial Court, through non-litigation through online mediation, and finally through YouTube's instrument is in the form of reporting copyright violations.